Challenges to Central Banking from Globalized Financial Systems - Schaechter, Andrea (International Monetary Fund, 2004)
Increasing global financial market integration is presenting new challenges to central banks as they seek to attain low inflation and financial stability. This volume is based on a conference hosted by the IMF in September 2002. It examines key issues such as the choice of nominal anchor for countries susceptible to shifts in capital flows, what can be done to prevent and deal decisively with financial crises, and how central bankers should think about the difficult choices when monetary objectives and financial stability objectives come into conflict.